Faktor Dominan Penyebab Addendum dan Pengaruhnya terhadap Kinerja Waktu Pelaksanaan Proyek Konstruksi di Provinsi Papua Pegunungan - Weya, Jean Marlin (Riwayat: Educational Journal of History and Humanities, 2025)
Contruction development in Indeonesia is currently growing rapidly in all fields, be it construction of roads and bridge construction as well as building construction. However, in the implementation of a contruction activity, several changes are often encounetered in its implementation. An addendum is an additional document prepared after the main contract is signed, with the aim of changing, adding to, or clarifying the contract. Contract addendum in construction projects are consequence of the dynamics of implementation that are not fully can be planned at the beginning. Various factor, both internal and external, can trigger the need for changes to the content of the contract through the issuance of an addendum. This research aims to determine the dominant factor causing addendum and their effect on the time performance of construction projects in Papua Pegunungan Provinve. This research uses a survey method in the form of distributing questionnaires to 40 respondents, namely consultants and contractors. Then the data analysis was carried out using Descriptive Statistical methods dan Relative Importance Index (RII). The result of the research show that the dominan factor causing addendum is road access to the project implementation location with a mean value 3,55 and RII value of 0,75. This is different from the causes of addendum pn other regions because Papua Pegunungan has difficult terrain and unique natural conditions.